Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1349-7006.2010.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging study of pancreatic ductal adenocarcinomas in Syrian hamsters using X‐ray micro‐computed tomography (CT)

Abstract: X-ray computed tomography (CT) has been used for diagnoses of human pancreatic cancer. Although micro-CT is a useful approach to evaluate macromorphology of organs ⁄ tissue also in animal models, reports on pancreatic tumors are limited. In this study, the utility of micro-CT was assessed in characterizing chemically induced pancreatic tumors in Syrian hamsters. Hamsters treated with or without N-nitrosobis(2-oxopropyl)amine (BOP) were injected with the antispasmodic agent, scopolamine butylbromide, and contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Using this technique, studies may be able to control the size of the pancreatic tumor quantitatively within an appropriate time period, a factor that demonstrates the usefulness of this model. With regard to studies that have used small animal models, Kitahashi et al (21) used micro-CT to detect chemically-induced pancreatic tumors of >4 mm in diameter in Syrian hamsters. Another study by Fendrich et al (18) detected precursor pancreatic adenocarcinoma lesions with an activity of 9.6±0.5 MBq in a five-month-old transgenic mouse model by FDG-PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Using this technique, studies may be able to control the size of the pancreatic tumor quantitatively within an appropriate time period, a factor that demonstrates the usefulness of this model. With regard to studies that have used small animal models, Kitahashi et al (21) used micro-CT to detect chemically-induced pancreatic tumors of >4 mm in diameter in Syrian hamsters. Another study by Fendrich et al (18) detected precursor pancreatic adenocarcinoma lesions with an activity of 9.6±0.5 MBq in a five-month-old transgenic mouse model by FDG-PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…11 In veterinary medicine, micro-CT has become a valuable in vitro tool for biological research as well as clinical diagnostics [12][13][14][15][16][17] and has proven to be beneficial as an in vivo diagnostic technique to visualize anatomical alterations as small as 30 mm in rodents and rabbits. 2,[18][19][20][21][22] Studies indicated that highresolution micro-CT can complement, if not replace, histopathology as the state-of-the-art standard in in vitro research and may become a viable part of in vivo clinical diagnostics. 2 The aim of the present case report was to determine the diagnostic yield of ex vivo micro-CT in a histopathologically confirmed canine oral fibrosarcoma that was removed by means of partial maxillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of ultrasound and contrast-enhanced magnetic resonance images (CE-MRI) are reported to be about around 100-200 mm. Micro-computed tomography (CT) and micro-MRI provide higher resolutions (< 50 mm), three-dimensional images and quantitative evaluation of angiogenesis, but a serious limitation is the limited ability for real-time analysis of blood flow dynamics (Savai et al, 2009;Kitahashi et al, 2010;Missbach-Guentner et al, 2011;Geffre et al, 2015). SR microangiography is potentially useful to assess and quantify intratumoral blood vessel morphology and blood flow dynamics in vivo more precisely, and with high resolution, spanning several centimeters visualization depth.…”
Section: Introductionmentioning
confidence: 99%